Impact of broadband speed on economic outputs: An empirical study of OECD countries - Chatchai Kongaut; Erik Bohlin (International Telecommunications Society (ITS), 2014)
Due to the development of new innovations and technologies, broadband services currently require more transmission capacity to work properly and efficiently with new content. Higher quality video content and more complex applications on internet services also require faster broadband speed. Hence, policy-makers have implemented broadband policy to ensure that countries will have high speed broadband infrastructure for both wired and wireless services. Even though the importance of broadband speed has been recognised almost everywhere, there are only a few studies investigating this issue in the academic field, especially in empirical research. In the past, a number of studies have analysed the impacts of broadband penetration on economic growth and indicated that higher broadband penetration leads to greater economic impacts. Nevertheless, other characteristics of broadband services such as different speeds of transmission, type of connection, quality of service and service providers are becoming more important to determine the economic impacts, as they vary across countries. Hence, broadband penetration on its own may not be a good measurement of the impacts of broadband services on the economy. This study therefore aims to add knowledge from a speed transmission perspective and enrich the empirical evidence in broadband speed studies, which has so far been limited. Similarly to the studies on the effects of telecommunication services (computer, mobile telephony and broadband penetration) on economic outputs, the estimated regressions of the model between broadband speed and economic outputs such as GDP are likely to suffer from endogeneity bias. To reduce the endogeneity problem, this study compares different models to provide the robustness of the relationship between broadband speed and economic outputs. This study also further analyses and compares the relationship between high and low income OECD countries. This paper applies the data from 2008 to 2012, mainly from the OECD and World Bank statistics, for most of the variables and the Ookla website for the broadband speed variable. The outcomes of this study are that broadband speed contributes positively to economic outputs such as GDP. The effects of broadband speed are also greater in countries with lower income. The policy recommendation is therefore that countries should focus on and encourage high speed broadband infrastructure and adoption in their national broadband plans and policies, which will ultimately lead to economic development.
Keywords: 330